A Database Framework for Expressing and Enforcing Personal Privacy Preferences - Basso, Tania; Piardi, Leandro; Moraes, Regina; Jino, Mario; Antunes, Nuno; Vieira, Marco (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2015: Anais do XVI Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2015.22941, 2015)
Nowadays, privacy protection in web applications and services is done, most times, through privacy policies that are presented to users and give them only the options of agreeing or disagreeing. So, it is not possible for users to express, in a detailed manner, their privacy preferences. Having this flexibility would allow users to make more thoughtful choices about the use of their personal information online. This paper proposes a database framework that allows users express their privacy preferences in detail, so that web applications can protect data privacy and manage personal information more securely. We tested the framework and results showed that it can be a simple and effective alternative, avoiding using complex and expensive solutions.